On the Control of Magnetic Anisotropy through an External Electric Field. Issue 43 (25th August 2014) - Goswami, Tamal; Misra, Anirban
Abstract: The effect of an external electric field on the magnetic anisotropy of a single‐molecule magnet has been investigated, for the first time, with the help of DFT. The application of an electric field can alter the magnetic anisotropy from "easy‐plane" to "easy‐axis" type. Excitation analysis performed through time‐dependent DFT predicts that the external electric field facilitates metal to π‐acceptor ligand charge transfer, leading to uniaxial magnetic anisotropy and concomitant spin Hall effect in a single molecule. Abstract : Outside influences on behavior : The effect of an external electric field on the magnetic anisotropy of a single‐molecule magnet has been investigated by DFT. The application of an external electric field triggers uniaxial magnetic anisotropy and result in spin‐Hall spatial spin separation in a cobalt(II)‐based pseudo‐octahedral complex (see figure).